2021
DOI: 10.1136/annrheumdis-2021-221160
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and experiences of individuals at-risk of rheumatoid arthritis (RA) knowing about their risk of developing RA and being offered preventive treatment: systematic review and thematic synthesis of qualitative studies

Abstract: ObjectivesThere is increasing interest in identifying individuals at-risk of rheumatoid arthritis (RA) and initiating early treatment to prevent or delay the onset of arthritis. We aimed to describe the perceptions and experiences of at-risk individuals and to inform the conduct of clinical trials and studies, and clinical practice.MethodsA systematic review and thematic synthesis of qualitative studies was conducted. Two review authors independently screened studies for inclusion, appraised their methodologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…Preventive behavioural/lifestyle interventions are also likely to be effective and may be preferred by patients. 13 The efficacy of lifestyle approaches to reduce the risk of RA development in at-risk groups and patient preferences for such an approach are important topics for further study. 47 …”
Section: Discussionmentioning
confidence: 99%
“…Preventive behavioural/lifestyle interventions are also likely to be effective and may be preferred by patients. 13 The efficacy of lifestyle approaches to reduce the risk of RA development in at-risk groups and patient preferences for such an approach are important topics for further study. 47 …”
Section: Discussionmentioning
confidence: 99%
“…Combined behavioural and pharmacological strategies may be effective in future clinical applications [ 43 ]. There is also converging evidence across qualitative studies that lifestyle interventions would be preferred over preventive drug therapies [ 20 ]. The efficacy of lifestyle approaches to prevent RA development [ 44 ] and preferences for such interventions are therefore important areas for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Among those at risk for RA, there is uncertainty regarding not only treatment effectiveness and safety, but also the individual’s risk of developing RA, the timeline for that risk and the severity of disease if RA does develop [ 19 ]. Qualitative studies have explored stakeholder perceptions of preventive treatment for RA [ 20 ]. A survey of individuals with arthralgia and autoantibody positivity found that 40% reported a willingness to accept preventive treatments that were 100% effective with minor side effects of immune suppression if their risk of developing RA was 70% [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perceptions of predictive approaches have been studied in those with CSA (43,48), asymptomatic individuals who have tested positive for RArelated autoantibodies (48), FDRs (44), the general public (49), and RA patients (who may be involved in providing access and/ or information to FDRs) (45). Participants across these studies recognized the value of disease risk information in terms of increased self-awareness and also the potential for early or preventive treatment (15). However, several studies noted concerns around the uncertainty associated with disease development and potential for psychological distress (44,45,48).…”
Section: Exploratory Qualitative Studiesmentioning
confidence: 99%
“…EULAR guidance for trials and observational studies in individuals at-risk of RA, based on expert consensus and evidence from systematic reviews (14,15), is now available and the scene is set for progress towards a new paradigm of prevention, rather than treatment of RA (16). Evaluation of candidate preventive therapies for RA is a nascent research area, though early findings are promising.…”
Section: Introductionmentioning
confidence: 99%